DYNAMICS OF IMPLEMENTATION OF THE ASSOCIATION AGREEMENT BETWEEN UKRAINE AND THE EU: PROSPECTS AND NEW CHALLENGES - Березовська, І. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2020)
Abstract. The entry into force of the Association Agreement with the European Union was a fateful event for the contemporary history of Ukraine. Currently, both components of the association: political one, which consists in spreading European values to Ukraine, and economic one, which involves Ukraine's integration into the EU internal market in exchange for legislation approximation, are without exaggeration fundamental factors for further development of Ukraine. The results of the previous years of the Association Agreement implementation testify to both significant achievements and a number of problems in Ukraine's fulfillment of its association with the EU “homework”. The article is devoted to the analysis of dynamics and the recent trends in the process of the Agreement implementation. As a result of the political changes that took place in Ukraine in 2019, including the election of a new president, parliament and government, European integration work on the implementation of the Association Agreement began in the new conditions. The improvement of the national institutional mechanism designed to ensure better coordination of work on the implementation of the Agreement between the competent authorities is among the positive trends in the process of its implementation. The fundamental legal principles and basic directions of work on Agreement updating are analyzed. It is proved that the prospect of updating has become an effective impetus to improve implementation processes. By initiating such an update, in order to strengthen its position in the negotiations with the EU, the Ukrainian side is forced to objectively assess the effectiveness of the Agreement implementation in certain areas and to intensify the completion of processes that are significantly behind. A new challenge in the process of implementing the Association Agreement was the emergence of the pandemic factor in 2020. The introduction of national quarantine and the incidence rate have significantly shifted priorities and affected European integration processes, both within Ukraine and at the EU level.At the same time, it was stressed that the situation to ensure the Rule of law, in particular, the fight against corruption is the main challenge not only to obligations fulfillment under the agreement, but also to the entire European integration policy of Ukraine. It is noted that thedecision of the Constitutional Court of Ukraine to repeal a significant part of anti-corruption legislation threatens the further integration of Ukraine with the EU. It was stressed that the future of not only Ukraine but also the region as a whole depends on whether the Association Agreement with the European Union will continue to serve as a transformational force capable of overcoming the weakness of the Rule of law within the country. Keywords: European Union, Association Agreement, implementation of association agreement, legislation approximation, rule of law, anti-corruption policy.

Аннотация. Вступления в силу Соглашения об ассоциации с Евросоюзом стало судьбоносным событием для новейшей истории Украины. На сегодня обе составляющие ассоциации: политическая, включаящая распространение на Украину европейских ценностей, и экономическая, предусматривающая интеграцию Украины во внутренний рынок ЕС в обмен на сближение законодательства, без преувеличения являются основополагающими факторами для дальнейшего развития Украины. Результаты предыдущих лет имплементации Соглашения об ассоциации свидетельствуют как о весомых достижениях, так и о ряде проблем в выполнении Украиной своего «домашнегозадания» ассоциации с ЕС. Статья посвящена анализу динамики и последних тенденций в процессе имплементации СА. Вследствие политических изменений, произошедших в Украине в 2019 году, включая избраниее нового президента, парламента и правительства, евроинтеграционная работа по имплементации Соглашения об ассоциации начала осуществляться в новых условиях. Среди положительных тенденций процесса имплементации соглашения отмечено усовершенствование национального институционального механизма, направленное на улучшение координации работы по выполнению соглашения между компетентными органами. Проанализированы правовые основы и основные направления обновления соглашения. При этом доказано, что перспектива обновления стала действенным стимулом к совершенствованию процессов имплементации. Инициируя такое обновление украинская сторона для укрепления своих позиций на переговорах с ЕС вынуждена объективно оценить эффективность выполнения соглашения по отдельным сферам и активизировать завершения процессов, по которым имеет место значительное отставание. Новым вызовом в процессе имплементации Соглашения об ассоциации стало появление в 2020 году фактора пандемии. Введение национального карантина и рост заболеваемости существенным образом сместили приоритеты и повлияли на евроинтеграционные процессы, как внутри Украины, так и на уровне Евросоюза. Наряду с этим подчеркнуто, что основным вызовом не только выполнению обязательств по соглашению, но и всей евроинтеграционной политике Украины стала ситуация с обеспечением верховенства права, в частности, проблема борьбы с коррупцией. Отмечено, что принятие Конституционным судом Украины решения об отмене значительной части антикоррупционного законодательства ставит под угрозу дальнейшую интеграцию Украины с ЕС. Подчеркнуто, что будущее не только Украины, но и всего региона зависит от того, продолжит ли Соглашение об ассоциации с Евросоюзом служить трансформационной силой, способной преодолеть слабость основ верховенства права внутри страны. Ключевые слова: Европейский союз, соглашение об ассоциации, имплементация соглашения об ассоциации, приближение законодательства, верховенство права, антикоррупционная политика.

Анотація. Набрання чинності Угодою про асоціацію з Євросоюзом стало доленосною подією для новітньої історії України. На сьогодні обидві складові асоціації: політична, що полягає в поширенні на Україну європейських цінностей, та економічна, що передбачає інтеграцію України до внутрішнього ринку ЄС в обмін на наближення законодавства, без перебільшення є основоположними чинниками для подальшого розвитку України. Результати попередніх років імплементації Угоди про асоціацію свідчать як про вагомі здобутки, так і про низку проблем у виконанні Україною свого “домашнього завдання” асоціації з ЄС. Статтю присвячено аналізу динаміки та останніх тенденцій в процесі імплементації Угоди про асоціацію. Внаслідок політичних змін, що відбулися в Україні в 2019 році, включно з обранням нового президента, парламенту та уряду, євроінтеграційна робота з імплементації Угоди про асоціацію почала здійснюватися в нових умовах. Серед позитивних тенденцій процесу імплементації угоди відзначено вдосконалення національного інституційного механізму, покликане забезпечити кращу координацію роботи з виконання угоди між компетентними органами. Проаналізовано правові засади та основні напрямки роботи з оновлення угоди. При цьому доведено, що перспектива оновлення стала дієвим стимулом до вдосконалення процесів імплементації. Ініціюючи таке оновлення українська сторона для зміцнення своїх позицій на переговорах з ЄС змушена об’єктивно оцінити ефективність виконання угоди за окремими сферами та активізувати завершення процесів, по яким є суттєве відставання. Новим викликом в процесі імплементації Угоди про асоціацію стала поява в 2020 році фактору пандемії. Запровадження національного карантину та ріст захворюваності істотним чином змістили пріоритети та вплинули на євроінтеграційні процеси, як в середині України, так і на рівні Євросоюзу. Поряд з цим підкреслено, що основним викликом не лише виконанню зобов’язань за угодою, а й всій євроінтеграційній політиці України стала ситуація із забезпеченням верховенства права, зокрема, боротьбою з корупцією. Відзначено, що прийняття Конституційним судом України рішення щодо скасування вагомої частини антикорупційного законодавства ставить під загрозу подальшу інтеграцію України з ЄС. Підкреслено, що майбутнє не лише України, а й всього регіону залежить від того, чи продовжить Угода про асоціацію з Євросоюзом служити трансформаційною силою, здатною подолати слабкість основ верховенства права всередині країни. Ключові слова: Європейський союз, угода про асоціацію, імплементація угоди про асоціацію, наближення законодавства, верховенство права, антикорупційна політика.
ДИНАМИКА ИМПЛЕМЕНТАЦИИ СОГЛАШЕНИЯ ОБ АССОЦИАЦИИ УКРАИНЫ С ЕС: ПЕРСПЕКТИВЫ И НОВЫЕ ВЫЗОВЫ
ДИНАМІКА ІМПЛЕМЕНТАЦІЇ УГОДИ ПРО АСОЦІАЦІЮ УКРАЇНИ З ЄС: ПЕРСПЕКТИВИ ТА НОВІ ВИКЛИКИ